Investigation of Glucose Sensing Based on Graphene Conductance. Issue 3 (1st January 2023) - Guo, Zeling; Fang, Bin; Du, Xiaowei; Zhao, Li; Li, Xinyu; Cao, Zhixiong; Huang, Xuelong; Sheng, Yaohuan; Zhong, Juan; Zhao, Gaowei; Zeng, Xiangfu; Zhao, Weidong; et al.
Abstract : Glucose sensing based on graphene conductance is investigated by the probe station and COMSOL Multiphysics. The current–voltage ( I–V) results from the probe station show that there is a negative linear relationship between graphene conductance and glucose concentration. Using this relationship as the standard curve, the concentration of glucose on graphene can be obtained by measuring the conductance of graphene. The electrical behaviors of different glucose molecules on graphene simulated by COMSOL Multiphysics Toolbox indicate a scattering effect of glucose molecules on current and a more rapidly linear potential drop in the glucose region calculated from the equipotential line distribution, which is consistent with the experimental results. These results provide a new research perspective and method for the sensing of glucose and other biological substances. Abstract : A new method is proposed for detecting glucose concentration based on graphene conductance. There is a negative linear relationship between graphene conductance and glucose concentration from the current–voltage characteristics. The simulation results of COMSOL Multiphysics indicate a scattering effect of glucose molecules on current and a more rapid linear potential drop in glucose region calculated from equipotential line distribution.